Stem cell approaches for diabetes: towards beta cell replacement - Weir, Gordon C (BioMed Central, 2011)
Stem cells hold great promise for pancreatic beta cell replacement therapy for diabetes. In type 1 diabetes, beta cells are mostly destroyed, and in type 2 diabetes beta cell numbers are reduced by 40% to 60%. The proof-of-principle that cellular transplants of pancreatic islets, which contain insulin-secreting beta cells, can reverse the hyperglycemia of type 1 diabetes has been established, and there is now a need to find an adequate source of islet cells. Human embryonic stem cells can be directed to become fully developed beta cells and there is expectation that induced pluripotent stem (iPS) cells can be similarly directed. iPS cells can also be generated from patients with diabetes to allow studies of the genomics and pathogenesis of the disease. Some alternative approaches for replacing beta cells include finding ways to enhance the replication of existing beta cells, stimulating neogenesis (the formation of new islets in postnatal life), and reprogramming of pancreatic exocrine cells to insulin-producing cells. Stem-cell-based approaches could also be used for modulation of the immune system in type 1 diabetes, or to address the problems of obesity and insulin resistance in type 2 diabetes. Herein, we review recent advances in our understanding of diabetes and beta cell biology at the genomic level, and we discuss how stem-cell-based approaches might be used for replacing beta cells and for treating diabetes.